Protein Intake, IGF-1 Concentrations, and Growth in the Second Year of Life in Children Receiving Growing Up Milk – Lite (GUMLi) or Cow's Milk (CM) Intervention - Lovell, Amy L.; Milne, Tania; Matsuyama, Misa; Hill, Rebecca J.; Davies, Peter S. W.; Grant, Cameron C.; Wall, Clare R. (Frontiers in Nutrition, 2021)
The relationship of protein intake with insulin-like growth factor 1 (IGF-1) concentrations in well-nourished children during the second year of life is poorly understood. The aim of this study was to explore the effect of a reduced-protein Growing Up Milk Lite (GUMLi) or unfortified cow’s milk (CM) on protein intake, growth, and plasma IGF-1 at 2 y. An exploratory analysis of a sample of Auckland-based children (n=106) in the GUMLi trial (a double-blind, randomised control trial, N=160) completed in Auckland and Brisbane (2015-2017). One-year old children were randomised to receive a reduced-protein GUMLi (1.7 g protein/100 mL) or a non-fortified CM (3.1 g protein/100 mL) for 12 months. Blood sampling and anthropometric measurements were made at 1 and 2 y. Diet was assessed using a validated food frequency questionnaire. Total protein intake (g/d) from CM was 4.6 g (95% CI: -6.7, -2.4; p<0.005) lower in the GUMLi group after 12 months of the intervention, with a significant group-by-time interaction (p=0.005). Length-for-age (LAZ) and weight-for-length (WLZ) z-scores did not differ between groups, however, mean body fat % (BF%) was 3.2% (95%CI: -6.2, -0.3; p=0.032) lower in the GUMLi group at 2 y. Mean plasma IGF-1 concentrations increased over time in both groups, with no group-by-time interaction (p=0.698). After combining the groups, IGF-1 concentration at 2 y. was positively correlated with %Energy Intake (%EI) from protein (p=0.03), g protein/1000 kcal (p=0.03), and LAZ (p=0.04) and independently associated with total protein intake (g/d) from CM (p=0.03). Reduced protein GUMLi resulted in lower %BF and lower total protein intakes but had no effect on growth parameters. Plasma IGF-1 concentrations were independently associated with total protein intake from CM at 2 y., highlighting an area of the diet to target when designing future protein-related nutrition interventions.